NEW DELHI METALLO-BETA-LACTAMASE PRODUCING CARBAPENEM-RESISTANT GRAM-NEGATIVE BACILLI: MICROBIOLOGICAL AND GENOTYPIC ANALYSES AT A TERTIARY CARE HOSPITAL IN PAKISTAN - Yunus, Faryal; Yunus, Faisel; Izhar, Mateen (Journal of Ayub Medical College Abbottabad, 2019)
Background: Metallo-beta-lactamases (MBL) catalyze the hydrolysis of beta-lactam antibiotics including carbapenems. A novel MBL subtype, New Delhi MBL (NDM), poses a serious public health problem. The aims of this study were to determine the frequency of NDM producers among the Carbapenem-resistant gram-negative bacilli (GNB) in hospitalized patients and carrying out the molecular analysis of the NDM genes as reliable data on this is not available in Pakistan. Methods: We carried out a cross-sectional study on prospectively collected clinical samples from 113 patients hospitalised at Shaikh Zayed Hospital Lahore, Pakistan. All the samples that were carbapenem-resistant on routine sensitivity testing were selected for this study. Various microbiological and genotypic analyses of the samples were performed. Results: The mean age of the patients was 47.8±20.8 years. About a quarter (25.7%) of the samples was from the urology ward and 43% were urine samples. Around two-third of the samples (n=74, 65.5%) tested positive for Non-Enterobacteriaceae GNB. Pseudomonas spp was the most common isolate among the Non-Enterobacteriaceae and E-coli amongst the Enterobacteriaceae. NDM gene was detected in 22 patients (19.5%). We did not find any association of the NDM gene with the demographic and clinical characteristics. Conclusion: NDM-positive GNB are present in our hospitalized patients, which is worrisome as these bacteria can disseminate globally and lead to an extensive and uncontrollable spread of pandemic clones for which efficient antibiotic therapy is currently not available. Systemic surveillance network and infection control strategies should be established to curtail dissemination of NDM-producing GNB in Pakistan. Keywords: Gram-Negative Bacteria; Extended Spectrum Beta Lactamase; New Delhi metallo-beta-lactamase; Carbapenem-Resistant Enterobacteriaceae; Health Care Associated Infections; Pakistan